Seismic drift demands of reinforced concrete buildings. - Shooshtari, Ahmad. (University of Ottawa (Canada), 1998)
A comprehensive analytical research has been conducted in the current study, which involved more than 350 analyses of R/C buildings in Canada, to gain insight into inelastic seismic drift demands of these buildings. The investigation consists of three major phases. The first phase includes the development of an improved version of an existing general purpose dynamic analysis software. The improvements consist of four major modifications; (a) implementation of a hysteretic model for P-M interaction effects, (b) implementation of a hysteretic model for masonry infill panels, (c) introduction of a new method to consider the P-$\Delta$ effect, and (d) introduction of a new feature to conduct inelastic static "Push-Over" analysis. The second phase involves a parametric study to establish importance of structural and ground motion parameters on seismic drift demands of R/C buildings. A 10-storey frame building, with and without reinforced concrete shear walls, was considered for the parametric study. An inventory of earthquake motions, consisting of 17 records, was selected for this purpose. The results indicated that inelastic shear, anchorage slip, P-$\Delta,$ and presence of masonry infills all played important roles on drift response. The P-M interaction on flexural behavior during response did not affect drift response for the structures considered. Therefore, this feature was not considered in the subsequent phase of the investigation, where inelastic drift demands were established. A total of 12 different types of buildings with different structural systems and heights were designed for response history analysis to establish seismic drift demands of R/C buildings. This constituted the third phase of the study. The structures considered included frame buildings with or without reinforced concrete shear walls and/or masonry walls. The current project also included an investigation on the credibility of push-over analysis as a tool for use in computing drift and ductility demands. It was found that its usefulness may be limited to structures behaving predominantly in the force mode. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.